2021
DOI: 10.1097/mat.0000000000001519
|View full text |Cite
|
Sign up to set email alerts
|

Limb Amputation Following Extracorporeal Membrane Oxygenation Therapy Among Survivors: A Nationwide Cohort Study from South Korea

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Of 28 SES studies, 14 studies (50%) were conducted outside the United States. Nine examined Income in the South Korean National Health Insurance (NHI), with four finding no association with ECMO complications or mortality (108)(109)(110)(111) and five reporting statistical associations without a consistent dose-dependent income response (112)(113)(114)(115)(116). One Chinese National Clinical Improvement System population-level study found that areas with mid-level Gross Domestic Product (vs high) had a lower mortality (117) and single-center study showed employment was associated with quality of life in survivors (118).…”
Section: Ecmo Outcomesmentioning
confidence: 99%
“…Of 28 SES studies, 14 studies (50%) were conducted outside the United States. Nine examined Income in the South Korean National Health Insurance (NHI), with four finding no association with ECMO complications or mortality (108)(109)(110)(111) and five reporting statistical associations without a consistent dose-dependent income response (112)(113)(114)(115)(116). One Chinese National Clinical Improvement System population-level study found that areas with mid-level Gross Domestic Product (vs high) had a lower mortality (117) and single-center study showed employment was associated with quality of life in survivors (118).…”
Section: Ecmo Outcomesmentioning
confidence: 99%